Pengaruh Perbandingan Tepung Talas Beneng (Xanthosoma undipesh K. Koch) dan Tepung Kacang Hijau (Vigna radiate) Terhadap Karakteristik Kukis Bebas Gluten - Mutiara, Ni Luh Gde Amritasya; Putra, I Nengah Kencana; Puspawati, Gusti Ayu Kadek Diah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 1 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i01.p10, 2024)
Cookies is a type of pastry made of a soft dough, a crunchy texture, and is less dense. In general, the ingredient to make cookies is flour which contains gluten, so some people, especially people with gluten intolerance, cannot consume it. Beneng taro flour can be used as an alternative which can produce gluten-free cookies. However, beneng taro flour has a low protein content, so mung bean flour must be added to the cookies to make up for this. In order to create gluten-free cookies with the best qualities, this study compares beneng taro flour and mung bean flour to see what effect it has. The completely randomized design (CRD) used in this study had a comparison treatment of beneng taro flour and mung bean flour that included 6 levels (100%:0%), (90%:10%), (80%:20%), (70%:30%), (60%:40%), and (50%:50%) that were repeated three times, resulting in 18 experimental units. The received data was examined using variance, and if it had a large impact, DMRT was then used. The best characteristics of gluten-free cookies were obtained from the treatment of 70% beneng taro flour and 30% mung bean flour with the criteria of protein content 9.32%, ash content 2.14%, water content 1.89%, fat content 34.53%, carbohydrates 52.12%, crude fiber content 4.83%, hardness 18.94 N, and sensory properties of liking aroma, slightly liking color, liking taste, liking texture, and overall acceptance of liking. The comparison of taro beneng flour and mung bean flour had a significant impact on the protein, ash, water, fat, carbohydrate, crude fiber, hardness, and hedonic tests on aroma, taste, color, texture, and overall acceptability (P 0.05), according to the results.